PENGEMBANGAN E-MODULE KIMIA BERBASIS EXE-LEARNING PADA MATERI LAJU REAKSI - Edolfin Manulang; Roza Linda; Asmadi M. Noer (Jurnal Pendidikan Kimia Universitas Riau, 2020)
This study was conducted only to the extent development, according of this research to develop and produce electronic module exe-learning based on reaction rates that is valid for use in learning based on ratings validator. The research was designed by research design with Plomp design which consist of four (4) steps; (1) preliminary investigation, (2) design, (3) realization, and (4) validation, evaluation, revision. The data are the assessment by the validator teams, teachers and learners’ respondent. The aspects of the assessment which are material substance, educational design, appearance and software. From the research, it gained validation value with score 94,35% from media validator and 88,12% from material validators. User response scores by teachers and learners were obtained 92,7% and 92%, respectively with very good criteria.